Acute kidney injury due to cytokine storm in patients with COVID-19 infection - Sepehr Ebrahimi-Dehkordi; Hasan Banitalebi; Ali Hasanpour-Dehkordi (Journal of Nephropathology, 2021)
Patients with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) or COVID-19 represents usually a variety range of symptoms related to influenza-like syndrome and respiratory tract infections. Likewise, kidney involvement and acute kidney injury (AKI) were reported in many previous studies. Although a hypovolemic circulation would be the most common reason in patients with AKI, some strong proofs are suggesting a cytokine storm due to immune system exaggeration and inflammation-mediated tubular injury in COVID-19 infections. The inflammatory response in cytokine storm leads to the high release of cytokines mostly including TNFα, IL-1β, IL-6, INFγ, IL-2, IL-7, and endothelial mediators. The main culprits in the AKI and consequent organ failure are resident leukocytes in specific tissues, activated following the cytokine release, and systemic inflammatory response. AKI management and cytokine profile evaluation should be highly emphasized in patients with COVID-19 to prevent the progression of chronic kidney disease or permanent renal failure. Treatment options in COVID-19 regarding no specific drugs should be supportive and based on stabilizing the patients; however, combination therapy with different antiviral have shown promising outcomes. As a result, utilizing the anti-TNFα and anti-IL-1 agents should be noticed if indicated. Additionally, the hematopoietic stem cell transplantation is a curative approach.